Handbook of medical imaging. Volume 3, - Kim, Yongmin; Horii, Steven C. (SPIE Press, 2000)
This volume describes concurrent engineering developments that affect or are expected to influence future development of digital diagnostic imaging. It also covers current developments in Picture Archiving and Communications System (PACS) technology, with particular emphasis on integration of emerging imaging technologies into the hospital environment.
Keywords: Diagnostic imaging -- Handbooks, manuals, etc.; Imaging systems in medicine -- Handbooks, manuals, etc.; Diagnostic imaging.; elektronické knihy; electronic books